Comparison of tonsil-oral-scrubbing with serum, oral fluid, and tonsil scraping to detect PRRSV RNA in sows over time following live virus inoculation - Li, Peng; Petznick, Thomas; Pratt, Emily; Cezar, Guilherme; Will, Kelly; Mil-Homens, Mafalda; Tong, Hao; Machado, Isadora; Moraes, Daniel C. A.; Paiva, Rodrigo C.; Berte, Alexis; Osemeke, Onyekachukwu H.; et al. (Frontiers in Veterinary Science, 2024)
IntroductionCurrent common sample types for sows, such as serum and tonsil scraping, require snaring the animals, which can be labor-intensive and raise concerns regarding animal welfare. Obtaining oral fluids (OF) from individual sows in field conditions presents challenges, as not all sows readily respond to the rope method. The Tonsil-Oral-Scrubbing (TOSc) collector allows for the rapid retrieval of fluids from the sow’s oral and tonsillar areas without the need for snaring. Previous studies have reported comparable detection rates of porcine reproductive and respiratory syndrome virus (PRRSV) RNA between TOSc and tonsil scraping, with significantly higher positivity observed in TOSc compared to serum in acutely infected sows.MethodsGiven that PRRSV RNA detection rates can vary among different sample types and fluctuate over time, this field study aimed to compare PRRSV real-time reverse-transcription polymerase chain reaction (RT-rtPCR) positivity and cycle threshold (Ct) values between TOSc, serum, OF, and tonsil scraping at three time points following live-virus inoculation (LVI) in sows. This study was conducted within a breeding herd attempting to eliminate PRRSV following an outbreak. Four sample types were collected from each of the 61 conveniently selected sows at 30, 60, and 90 days post-LVI in the order of OF, TOSc, tonsil scraping, and serum, and subsequently tested for PRRSV RNA.ResultsThe results indicated that TOSc and tonsil scraping exhibited decreased PRRSV RNA detection rates over time, whereas the detection rates for OF and serum remained relatively stable. Moreover, the median Ct values for TOSc and tonsil scraping were numerically lower than those for OF and serum at all sampling points. Specifically, tonsil scraping demonstrated significantly higher PRRSV RNA positivity than the other three sample types. TOSc also exhibited significantly higher PRRSV RNA positivity than OF and serum at both 30 and 60 days post-LVI. By 90 days post-LVI, there was a significant difference in the PRRSV RNA detection rates between TOSc and tonsil scraping. However, no significant difference was observed between TOSc and OF or between TOSc and serum. According to the RT-rtPCR results, most PRRSV RNA-positive sows detected via TOSc and tonsil scraping turned negative by 90 days post-LVI, although a small proportion remained positive. Conversely, a small number of previously negative sows tested positive at 60 and 90 days post-LVI, indicating an intermittent mode of PRRSV RNA detection for both sample types.